IMPLIKATUR PADA VIDEO UNGGAHAN BINTANG EMON TANGGAL 9 OKTOBER 2020 DI TWITTER - Ichan, Galuh Rahmah (Hasta Wiyata, 2023)
ABSTRACTThe article titled "Implicative Analysis of Bintang Emon's Video Upload on October 9, 2020, on Twitter" is a study that discusses the principle of implication in Bintang Emon's video that was uploaded via Twitter on October 9, 2020. The analysis of implicature in this paper aims to find out the actual meanings of criticism conveyed by Bintang Emon regarding the phenomenon of law enforcement. We can see this from the background of Bintang Emon, who is a stand-up comedian that active in voicing his criticism of political and social issues. The research method used is qualitative that focuses on the field of pragmatic discourse analysis with a theoretical basis developed by Sperber and Wilson (2008). Through this research, the researcher finds out that the speech on Bintang Emon's video on October 9, 2020, contains the principle of implicature with contextual meaning that is influenced by situation, place, time, and environment. The video uploaded by Bintang Emon on his Twitter account on October 9, 2020, is a form of his reaction to comments regarding the issue of the Omnibus Law which has mentioned his name on various social media sites. In the video, Bintang Emon uses a form of satire as a criticism of the government. Therefore, this is the background of the implicative in his speech.Key Words : Implicative, Bintang Emon, RUU